Luminescence and photocatalytic studies of Sm3+ ion doped SnO2 nanoparticles - Singh, L. P.; Luwang, Meitram Niraj; Srivastava, S. K. (New Journal of Chemistry, 2014)
Sm3+ ion doped tetragonal SnO2 nanoparticles have been synthesized by the polyol method and its concentration and annealing effects on photoluminescence properties are studied. The XRD results show the changes of lattice parameters with the incorporation of the Sm3+ ion into the SnO2 host lattices. Fourier transform infrared (FTIR) data indicate the formation of a Sn-O bond and capping of the nanoparticles by ethylene glycol. The broad emission peaks observed around 350 to 550 nm are attributed to the emission from defects or traps present in the host SnO2. The typical emission peaks of the Sm3+ ion are observed and there is efficient energy transfer between the host, SnO2 and the dopant, Sm3+ ion. Further, the prepared samples are experimented towards the photocatalytic behavior on selected triphenylmethane dyes, Ethyl Violet (EV) and Brilliant Green (BG). The degradation of dyes was found to be enhancing in the presence of Sm3+ ions as it suppress the e e(CB)(-) and h(VB)(+) recombination.

Microemulsion mediated synthesis of triangular shape SnO2 nanoparticles: luminescence application - Luwang, Meitram Niraj (Applied Surface Science, 2014)
The triangular prism shapes of SnO2 center dot xH(2)O nanoparticles are prepared using microemulsion route. The effect of variation of water pool value on the formation of SnO2 nanoparticles was studied. There is the quantum size effect in absorption study of SnO2 nanoparticles. With the increase of the water pool value, there is a decrease in the band edge absorption energy suggesting the weak quantum confinement effect (QCE) in SnO2 nanoparticles. Quenching effect increases with increase of water to surfactant ratio in luminescence. There is no significant effect in lifetime values for SnO2 nanoparticles in both microemulsion and powder form. SnO2 nanoparticles show green emission due to oxygen vacancy. SnO2 nanoparticles when doped with Eu3+ ions give the enhanced luminescence of Eu3+ due to the surface mediated energy transfer from SnO2 to Eu3+ ion. (C) 2013 Elsevier B. V. All rights reserved.
Keywords: Microemulsion; Theoretical particle size calculation; Triangular nanoparticles

Novel synthesis and characterization of CuO nanomaterials: biological applications - Devi, Ayekpam Bimolini; Moirangthem, Dinesh Singh; Talukdar, Narayan Chandra; Devi, M. Damayanti; Singh, N. Rajen; Luwang, Meitram Niraj (Chinese Chemical Letters, 2014)
CuO nanoparticles were synthesized at a relatively low temperature (80 degrees C) for 2 h using polyethylene glycol-glycerol mixture which acts as a capping agent. A detailed characterization of the synthesized nanomaterials were performed utilizing X-ray diffraction (XRD), infra-red spectroscopy (IR), thermogravimetric analysis (TGA-DTA), transmission electron microscopy (TEM), photoluminescence (PL) by studying its crystalline phase, vibrational mode, thermal analysis, morphology and photoluminescence properties. The effect of annealing on the as-prepared nanoparticles were studied and compared with their corresponding bulk counterpart. The synthesized nanoparticles have been screened for in vitro cytotoxicity (IC50) studies against the human cervical adenocarcinoma cell line (HeLa) using MTT assay methods. The as-prepared nanoparticle inhibits the proliferation of this HeLa cell. The standard disc diffusion method has been used to study the antibacterial activity of the samples against the human pathogenic bacteria Escherichia coli (MTCC 729), Proteus mirabilis (MTCC 425) and Klebsiella pneumoniae subsp. pneumoniae (MTCC 432). The results have been compared with the positive control antibiotic gentamycin. The synthesized nanoparticles would provide a potential alternative to antibiotics for controlling some of the microorganisms causing urolithiasis. (C) 2014 Meitram Niraj Luwang. Published by Elsevier B.V. on behalf of Chinese Chemical Society. All rights reserved.
Keywords: Annealing; Antibacterials; CuO nanoparticles; Cytotoxicity; HeLa cell lines

Arsenic detection in water: YPO4:Eu3+ nanoparticles - Ghosh, Debasish; Luwang, Meitram Niraj (Journal of Solid State Chemistry, 2015)
This work reports on the novel technique of detection of arsenic in aqueous solution utilising the luminescence properties of lanthanide doped nanomaterials. Eu3+ (5%) doped YPO(4)nanorodswere utilised for the said experiment. Co-precipitation method was used for the synthesis of the materials and characterised them with different instrumental techniques like X-ray diffraction (XRD), Infra-red (IR), UV-absorption, scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray photoelectron spectroscopy (XPS) and photoluminescence studies. This nanoparticle can adsorb both arsenic and arsenious acids. We studied the effect of arsenic adsorption on the luminescence behaviour of the nanoparticles. Arsenic acid enhanced the luminescence intensity whereas arsenious acid quenched the luminescence. This luminescence enhancement or quenching is related with arsenic concentration. This relation of luminescence property with concentration of arsenic can be used to detect arsenic in industrial waste. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Arsenic detection; Luminescence; Nanomaterials

One-pot synthesis of 2-thenoyltrifluoroacetone surface functionalised SrF2:Eu3+ nanoparticles: trace level detection of water - Ghosh, Debasish; Luwang, Meitram Niraj (RSC Advances, 2015)
This work reports the one pot synthesis of 2-thenoyltrifluoroacetone (TTA) surface functionalised SrF2:Eu3+ nanoparticles. The nanoparticles were characterised by X-ray diffraction (XRD), infra-red (IR), UV-absorption, transmission electron microscopy (TEM), and photoluminescence studies. Sensitization of Eu3+ ion by TTA in SrF2 nanoparticle matrix gives an enhanced luminescence in dry aprotic solvents like tetrahydrofuran (THF), acetonitrile (AN), dichloromethane (DCM) etc. We studied the effect of trace quantity of water on luminescence of the particles in THF solvent. Even a trace level of water content in the solvent is able to quench the luminescence significantly and quenching enhances with addition of more and more water. This approach of luminescence quenching strategy of detecting a minute trace level of water molecules has a potential application in the estimation of water in various dry organic solvents like THF.

p-Aminobenzoic acid (pABA) sensitization of LaF3:Tb3+ nanoparticles and its applications in the detection of explosive materials - Ghosh, Debasish; Luwang, Meitram Niraj (RSC Advances, 2015)
This work reports the utilization of water dispersible terbium (Tb3+) doped spherical LaF3 nanoparticles (similar to 5 nm) surface functionalised with p-aminobenzoic acid (pABA) for the detection of aromatic nitro explosives. The functionalised nanoparticles show remarkable sensitivity to a number of highly electron deficient aromatic nitro compounds like picric acid (PA), 2,4,6-trinitrotoluene (TNT), 2,4-dinitrotoluene (2,4-DNT), 2,4-dinitrophenol (2,4-DNP) etc. All of these nitro compounds can be detected easily at ppm level using this luminescence quenching technique whereas in the case of TNT it can detect concentrations as low as 50 ppb. This novel approach of utilising the Tb3+ doped NPs sensitised by pABA has potential application in the detection of explosive materials.

Catalytic activity of bare and porous palladium nanostructures in the reduction of 4-nitrophenol - Kalekar, Ajit M.; Sharma, Kiran Kumar K.; Luwang, Meitram Niraj; Sharma, Geeta K. (RSC Advances, 2016)
The catalytic activity of bare and porous palladium nanostructures viz. palladium nanoballs (PdNBs) and palladium urchins (Pdurc) synthesized in surfactant based liquid crystalline mesophase have been investigated in the reduction of 4-nitrophenol. The loading of PdNBs and Pdurc nanocatalyst in the reaction are optimized to 1.57 x 10(-4) mol% and 1.57 x 10(-3) mol% respectively. The surface area normalized rate constant obtained at 303 K for PdNBs (0.74 +/- 0.03) s(-1) m(-2) L and Pdurc (0.41 +/- 0.05) s(-1) m(-2) L is the highest, considering the low palladium loading used in the reaction. The specific surface area determined for the PdNBs and Pdurc are 153 m(2) g(-1) and 27 m(2) g(-1) respectively. The high surface area of PdNBs nanostructure is consistent with the highest catalytic activity. The palladium nanostructure catalyzed reaction lacks induction time (t(0)), indicating the influence of porosity in the Langmuir-Hinshelwood mechanism. Besides, PdNBs and Pdurc exhibited thermal stability and structural integrity with good conversion of the substrate (>97%) even up to five consecutive reactions. The mechanistic insight of the bare and porous palladium nanostructures presented in this study is significant for the development of stable and efficient palladium metal based nanocatalyst.

Selective detection of Fe3+, Cr3+ and Cu2+ in water using highly luminescent Gd2O3:Eu3+ nanoparticles - Ghosh, Debasish; Luwang, Meitram Niraj (Journal of Luminescence, 2016)
Rod shaped Eu3+ doped Gd2O3 nanoparticles were synthesised by a simple wet-chemical method followed by high temperature heating at 700 degrees C. The nanoparticles were characterised by X-ray diffraction (XRD), infra-red (IR), transmission electron microscopy (TEM), x-ray photonelectron spectroscopy (XPS), photoluminescence (PL) studies and lifetime measurement. The particles show strong host sensitised luminescence in water. Luminescence in water is selectively quenched by Fe3+, Cr3+ and Cu2+ ions. This luminescence quenching phenomenon has been utilised to detect metal ions in synthetic water and environmental water samples. Results obtained by luminescence quenching for environmental water samples are in good agreement with the results obtained from inductively coupled plasma atomic emission spectroscopy (ICP-AES) study. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Detection; Luminescence; Nanoparticles; Quenching; Sensitization

Synthesis of nanogate structure in GO-ZnS sandwich material - Kumar, Praveen; Luwang, Meitram Niraj (Scientific Reports, 2019)
Graphite Oxide (multi-layer) composite with other materials has a huge application in various field of science, due to its excellent and unique properties. Even though from past decade, immense research has been done by materials scientists in this field, but the chemistry is still not yet satisfactory. Here, in this work, through the discovery of Nanogate structure, we have reported for the first time the experimental results that enlightened the clear chemistry between the GO and ZnS which is further supported by the DFT calculations. This novel synthesis method led to the discovery of nanogate structure sandwiched between the GO layers. The nanogate formation also shows enhanced properties for various applications like photocatalytic activities, etc. Due to the nanogate formation, there might be a possibility of enormous generation of electrons on excitation of the composite materials, which can be a boom for various applications like photocatalysis, water splitting, solar cell, etc.

Magnetic and luminescent multifunctional nanohybrid: Fe3O4@CaF2:Tb3+: a facile synthesis and characterization - Vats, Monika; Kumar, Rakesh; Sharma, Jyotsna; Luwang, Meitram Niraj (Indian Journal of Pure & Applied Physics, 2020)
In the present study, bi-functional hybrid nanomaterial has been synthesized and characterized via facile method and characterized. The synthesized nanomaterial shows both magnetic and luminescent properties which are confirmed by VSM (vibrating sample magnetometer), UV-Vis spectra and the photoluminescence emission spectra. For the magnetic phase, i.e., nanocrystalline magnetite, Fe3O4 is used as the core which is then functionalized using polyethylene glycol (PEG) and for the luminescent phase, polyethylenimine (PEI) functionalized CaF2 doped with Tb3+ is used as the emitter. Wherein, both PEG and PEI serve the dual purpose of functionalization as well as stabilization by steric repulsion. The structure and morphology of the synthesized bifunctional hybrid nanomaterial are studied with the help of scanning electron microscopy (SEM) and X-ray powder diffraction.
Keywords: Biocompatible; CaF2; Co-precipitation; Fe3O4; Luminescent nanoparticle; Magnetic nanoparticles; Nanohybrid; Tb3+ doping

Deciphering the role of temperature in Li+ co-dopant occupancy in BaYF5:Yb3+,Er3+ up-converting nanocrystals and its structure-property relationship - Devi, Suman; Luwang, Meitram Niraj (Journal of Chemical Physics, 2021)
Precision engineering of defects in luminescent nanoscale crystalline materials with lesser controls to design is an area of interest in engineering materials with desired properties. Li+ co-doped BaYF5 nanocrystals were engineered, and temperature as controls for determining the co-dopant occupancies in the host lattice is studied. An observed enhancement in the up-conversion photoluminescence results from the co-dopant occupancy at Ba2+ sites via substitution through the hot injection method, whereas for samples prepared using co-precipitation, photoluminescence quenching was observed, which can be correlated with the Li+ occupancy at the interstitial site near Er3+ and also due to the incorporation of OH-. The crystal lattice deformation as a result of doping and the mechanism for the observed enhancement/quenching of luminescence are studied using x-ray diffraction, x-ray photoelectron spectroscopy, and energy transfer mechanism. Cytotoxicity assay and photoluminescence studies of the synthesized nanocrystals confirm that the material is biocompatible.

CdS cubane type clusters encapsulated by rolling of single layer reduced graphene oxide sheets for enhanced mechanical energy harvesting - Kumar, Praveen; Ram, Farsa; Shanmuganathan, Kadhiravan; Luwang, Meitram Niraj (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Composites with Single Layer Graphene Oxide (SLGO) sheets are extremely difficult to achieve, irrespective of the current advancements in graphene composites research. The difficulties in exfoliating the graphite oxide (GO) was associated with a strong interaction among the edge sides of the adjacent layers. This in-turn barricades the foreign intruders to interact with the basal plane, thereby restraining one to form composites with SLGO sheets. In this work, we had successfully exfoliated GO through a spacer [Cd(OAc)(2) + polyethylene glycol (PEG)] to result in nano-engineered CdS cubane-type clusters in rolled up SLGO to form graphene oxide complex compound (GOCC), resembling carbon nanotubes (CNTs). The CdS cubane-type clusters were found to interacting with the carbon skeleton of rolled reduced SLGO sheet through a Manogate' structures, which was supported by density functional theory (DFT) calculations. Our theoretical study reveals that the obtained complex compound (GOCC) is thermodynamically more favourable than its ancestor materials (CdS cubane and empty CNT). Flexible piezoelectric nanogenerators (PENGs) fabricated from GOCC and thermoplastic polyurethane (TPU) resulted in output voltage (V-oc) of 4.5 V and output current of 0.4 mu A at applied force of 13 N. The nanoengineering helps to achieve superior mechanical energy harvesting performance for GOCC compared to pristine CdS, which demonstrate the potential of nanogate structures to enhance the intrinsic properties of materials.
Keywords: Graphene oxide complex compound; Nanogate structure; New material; Novel procedure; Piezoelectric nanogenerator; SLGO

Sulfur functionalization via epoxide ring opening on a reduced graphene oxide surface to form metal (II) Organo-bis-[1,2]-oxathiin - Kumar, Praveen; Bajpai, Himanshu; Gopinath, Chinnakonda S.; Luwang, Meitram Niraj (Inorganic Chemistry, 2022)
The epoxide ring-opening reaction in graphene oxide (GO) by nucleophiles is a very fascinating and advanced methodology to develop novel functional material. Herewith, we report an advanced strategy for opening the epoxide ring on the rGO surface via easily an available nucleophile (Na2S), which is further functionalized with O atom to obtain four-membered rings (FMRs). The Cd coordination with the S atom puts extra stress on the FMR leading to the C-C bond cleavage of the four-membered heteroatomic rings on the rGO surface. This strategic approach leads to the fabrication of an innovative metal organo-bis-[1,2]-oxathiin (MOBOT) chemical moiety (M = Cd, Zn). The MOBOT compound further shows enhanced H-2 generation activity and hence is promising as a potential photocatalyst for solar hydrogen generation. This compound might also be a potential candidate for optoelectronic applications.

Cadmium (II) Organo Tetrakis-[1,2]-Oxathiin (CdOTOT): a 3D sandwiched frameworks with efficient hydrogen production - Kumar, Praveen; Bajpai, Himanshu; Luwang, Meitram Niraj (Journal of Catalysis, 2023)
For over a decade, the structure, reactivity, and mechanism of graphene based photocatalysts have been of great interest for hydrogen (H2) generation. Several studies have been done on the edge side groups (ESGs) of graphene oxide (GO), but the basal plane groups (BPGs)-epoxide and hydroxide have acquired far less attention. This is because the GO layers are strongly held with van der waals forces as well as H-bonding which prevents the foreign body from entering inside the layers. To overcome these problems, this study presents the successful synthesis and application of four coordinated sandwiched (FCS) Cadmium (II) Organo Tetrakis-[1,2]-Oxathiin (CdOTOT) in rGO-CdS composite (A 3D sandwiched frame-work). Additionally, experimental outcomes have been further supported using density functional theory (DFT), which suggest that CdOTOT is more stable than its precursors as well as thermodynamically favourable. The CdOTOT shows high H2 production activity -67.5 mmol/g or 13.5 mmol/g/h in presence of 1 % Pt cocatalyst and sacrificial reagents (Na2S/Na2SO3). It is around 33 times higher than pristine CdS, and stable up to around 15 hrs without adding any cocatalyst. This mesmerising outcome is over with reported various CdS-rGO based photocatalysts. The higher activity was further explained through the proposed mechanism and observed low electronic work function of CdOTOT. This innovative and extend-able (with other metals) approach provides a revolutionary impact on numerous cutting-edge research applications like photocatalysis, water splitting, solar cell, etc.(c) 2022 Elsevier Inc. All rights reserved.
Keywords: 2]; 3D sandwiched frameworks; Basal Plane Groups (BPGs); Cadmium (II) Organo Tetrakis-[1; hydrogen production; Oxathiin (CdOTOT)

Tuning the optical properties of Ln3+-doped-Y2O3@ZnO@Au core-shell heterostructures for visible-to-NIR photon harvesting - Jayswal, Shefali; Luwang, Meitram Niraj; Moirangthem, Rakesh S. (Surfaces and Interfaces, 2024)
Here, compact Yb3+-Er3+-Tm3+ doped Y2O3 phosphor microspheres were synthesized by solvothermal method which gave emission in the entire visible region under 980 nm excitation. The effect of doping alkali ions like lithium on the upconversion emission of YYET phosphors is investigated. An epitaxial layer of ZnO is grown around the YYETL (Li+ doped YYET) microspheres by hydrothermal technique. An analysis of the influence of the ZnO shell thickness on the upconversion emission of core microspheres is done. Initial growth of a thin layer of ZnO on the YYETL microspheres causes enhancement in upconversion emission due to passivation of surface defects of core microspheres. Quenching of anti-Stokes emission occurs for thicker ZnO shell coating. Further, it is decorated with AuNPs to study the effect of plasmonics on the optical property of the developed heterostructure. The overlap between the upconversion emission spectra of core microspheres and the LSPR peak of AuNPs modulates the property of the entire structure. The optimized samples were checked for photocatalytic application by degradation of Rh6G dye under solar irradiation. YYETL@ZnO@Au core-shell samples exhibited highest rate constant of 0.00395 min(-1), which is attributed to better exploitation of the UV-Vis-NIR region of the solar spectrum by all three components of the heterostructure.
Keywords: AuNPs; Core-shell heterostructure; LRET; Photocatalysis; Upconversion microspheres; ZnO

Engineering luminescent carbon dot emission through surface state functional group via heteroatom doping and unveiling the effect of solvents - Devi, Suman; Luwang, Meitram Niraj (Langmuir, 2025)
This work comprehends the synthesis of carbon dots from papaya leaves (PCD) using water, ethanolamine (EA), and dimethylformamide (DMF). Ethylenediamine (EDA) was used to introduce nitrogen doping. Water-based PCDs emit blue light, while those in EA and DMF emit red light due to increased oxidation. In EA or DMF with EDA, red emission quenches, and enhanced blue emission is observed, which infers reduced oxidation. This indicates that EDA shifted the emission back to the blue. These findings were confirmed by hypothetical mechanistic studies, Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). The Raman spectrum revealed defect-activated D and G bands; defects increase in pure solvents compared to water but decreases in mixed solvents such as EA + EDA and DMF + EDA. In XPS, C-O bonds were detected at a higher level in EA and DMF, whereas C-N bonds were observed at a higher level in EDA. TEM images showed that the synthesized PCDs ranged from 1 to 5 nm, with interplanar spacing values consistent with X-ray diffraction (XRD) analysis. PCDs synthesized from a sustainable carbon source exhibit tunable fluorescence from blue to red and vice versa based on solvents used during the engineering of surface state functional group. This makes them promising candidates for fluorescent security inks.

Investigating the design of ssPalmO-derived lipid nanoparticles for mRNA delivery applications using molecular dynamics simulations - Barange, Anjana; Luwang, Meitram Niraj; Meena, Santosh Kumar (ACS Omega, 2025)
The rational design of lipid nanoparticles (LNPs) is essential for the effective transport of drugs and genetic material, as their structural and dynamic properties are heavily influenced by lipid composition and functional group modifications. In this study, we employed molecular dynamics simulations with density functional theory (DFT) derived force fields to investigate the bilayer properties of ssPalmO lipids, their phenyl ester (ssPalmO-phe) and benzyl ester (ssPalmO-ben) derivatives, as well as their cis and trans isomers. While all systems formed stable bilayers, cis-ssPalmO deviated by adopting a flexible, nonlamellar architecture. Trans isomers of ssPalmO-phe and ssPalmO-ben exhibited greater bilayer thickness, packing density, and order parameters due to stronger intramolecular chain interactions, while their aromatic substituents reduced lateral diffusion relative to ssPalmO. Trans isomers exhibited lower electrostatic potential differences, which increased upon incorporation of helper lipids, concomitantly enhancing bilayer packing and thickness while suppressing diffusion. These results clarify how lipid functionalization, stereochemistry, and helper lipid composition modulate bilayer organization, offering molecular level guidance for rational LNP design in drug and mRNA delivery.

Precursor-dependent heteroatom diversity in luminescent carbon quantum dots: their impact on physicochemical properties and free radical scavenging and antibacterial activities - Konwar, Pollab Mohan; Devi, Suman; Pandey, Satish Kumar; Devi, Khomdram Sandhyarani; Devi, Ayekpam Bimolini; Luwang, Meitram Niraj (Langmuir, 2025)
The fabrication of a multifunctional carbon quantum dot (CQD) from a novel carbon source is still continuing to be demanding and fascinating. The carbon precursor plays a crucial role in developing any particular properties of a CQD to suit a specific application. In this study, green (Rhus chinensis fruits) as well as chemical-based (ascorbic acid and urea) carbon sources were used for the fabrication of CQDs using a simple, cost-effective, and eco-friendly method. The various physicochemical and optical properties of R. chinensis fruit-derived CQD (CQD-RCF) and urea-assisted ascorbic acid-derived CQD (CQD-AAU) were thoroughly investigated by using multiple characterization techniques such as XRD, TEM, HR-TEM, Raman, XPS, FT-IR, UV-vis, PL, and zeta potential. The synthesized CQDs were screened for antioxidant properties by a DPPH assay and antibacterial activity by the agar tip-well method. Both of these synthesized CQDs exhibited a variety of dissimilarities regarding their heteroatom compositions and surface functional groups, which subsequently led to an enhanced DPPH radical scavenging efficacy of CQD-AAU and a declared antibacterial efficacy of CQD-RCF. Therefore, the outcome of this study shows that the physicochemical properties and functionalities of CQDs are influenced by the chemical composition of the precursor material.

Liquid crystalline nanoconfined growth of PANI on rGO for enhanced electrochemical glucose sensing - Tawade, Anita K.; Kumar, Praveen; Tayade, Shivaji N.; Sharma, Geetarani K.; Luwang, Meitram Niraj; Sharma, Kiran Kumar K. (Nanoscale, 2026)
We report here a new strategy for the successful synthesis of a hybrid 2D nanocomposite via the in situ functionalization of graphene oxide (GO) with aniline monomers in a bi-solvent swollen liquid crystalline lamellar mesophase (SLCLM) nanoreactor. The synthesized nanocomposite product revealed possible simultaneous reactions at the edge and basal plane of GO. A mechanism for the transformation via simultaneous nucleophilic attack and spontaneous polymerization, forming a reduced graphene oxide-polyaniline (rGO-PANI) nanocomposite, is proposed. The multistep plausible reaction mechanism for the functionalization of the GO edge -COOH group is achieved by successful synthesis, followed by isolation and characterization of the N-phenyl anthranilic acid derivative as an intermediate product. Furthermore, the detection of CO2 evolution as a by-product during the reaction complements the plausible mechanism for the incorporation of (-C Xi C-) graphyne-type edges and formation of new -C-N- and O-H bonds in the rGO-PANI nanocomposite. These results are supported by FT-IR, Raman, XPS, SAXS, and C-13 NMR spectroscopy analyses. A reduced graphene oxide-polyaniline (rGO-PANI) modified glassy carbon electrode was developed for glucose sensing, exhibiting a wide linear range (0.554-10 & micro;M), low detection limit (50 pM), and high sensitivity (372 660 & micro;A mM(-1) cm(-2)). The sensor demonstrated excellent selectivity against common interferents (ascorbic acid, uric acid, and dopamine), reproducibility (RSD < 5%), and stability over 10 000 s with minimal signal loss. The detection of glucose from human metabolites, such as urine and sweat, achieved 98-100% recoveries for spiked glucose, confirming its practical applicability. These results establish rGO-PANI as a robust platform for sensitive and selective glucose detection.